Knowledge and Compliance Regarding Central Line Associated Blood Stream Infections (CLABSIs) Prevention Among Public and Private Hospital Intensive Care Unit Nurses: Central Line Associated Blood Stream Infections - Yaseen, Muhammad; Suliman, Muhammad; ., Adnan; Yaseen, Mahnoor; Ali, Sardar; Sultan, Amir (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2022)
CLABSIs are some of the utmost fatal hospital-acquired infections. CLABSIs cost up to 45,000 per infection around the world. CDC reported that in U.S. hospitals around 41,000 preventable CLABSIs occur every year, so the magnitude of the problem could be worse in Pakistan where there are still gaps in documenting the hospital data. Objective: To identify the nurses’ knowledge and compliance and their association regarding prevention of CLABSI in public and private sector hospitals of Peshawar. Methods: An analytical cross-sectional study was carried out among 140 Nurses working in Intensive Care Units of (LRH & RMI) who had at least one year of experience. Enumerative or census sampling method was used to take the entire eligible ICU nurses as a sample. Data was collected through a validated and pre pilot tested questionnaire and checklist. Results: Around 30% of the nurses had poor knowledge, 43.6% had an average knowledge, 22.1% good knowledge and only 3.6% had an excellent knowledge regarding CLABSIs. The compliance level was found as 83.6%. Very weak positive association was found between knowledge and compliance level of nurses regarding CLABSIs on Pearson Correlation test (r). Conclusions: The results of this study concluded that nurses were not well equipped with the knowledge regarding CLABSIs, while there was a weak positive relationship between knowledge and compliance level among nurses. Therefore, the findings suggest that nurses need to be updated with standard guidelines and training to prevent CLABSIs.